Mga tinig mula sa ibaba kasaysayan ng Partido Komunista ng Pilipinas at Partido Sosialista ng Pilipinas sa awit, 1930-1955 - Maceda, Teresita Gimenez- (Diliman, Quezon City University of the Philippines Press and UP Center for Integrative and Development Studies, Peace, Conflict Resolution and Human Rights Program, 1996)
History of Philippines Communist Party and Philippines Socialist Party in songs.
Includes musical score with staff notation.
Includes bibliographical references (p. 223-229).
In Tagalog.
Keywords: Communist Party of the Philippines (1930- ) -- Songs and music -- History and criticism; Socialist Party (Pampanga, Philippines) -- Songs and music -- History and criticism; Revolutionary ballads and songs -- Philippines -- History and criticism; Songs, Tagalog -- Philippines -- History and criticism; Protest song -- Philippines; Radicalism -- Songs and music; Socialism -- Philippines